β-Cells Different Vulnerability to the Parkinsonian Neurotoxins Rotenone, 1-Methyl-4-phenylpyridinium (MPP+) and 6-Hydroxydopamine (6-OHDA) - Marco Carli; Francesca Vaglini; Eleonora Risaliti; Gianluca Citi; Matilde Masini; Shivakumar Kolachalam; Roberto Maggio; Giovanni Umberto Corsini; Michela Novelli; Vincenzo De Tata; Marco Scarselli (MDPI AG, 2021)
Neurotoxins such as rotenone, 1-methyl-4-phenylpyridinium (MPP+) and 6-hydroxydopamine (6-OHDA) are well known for their high toxicity on dopaminergic neurons and are associated with Parkinson's disease (PD) in murine models and humans. In addition, PD patients often have glucose intolerance and may develop type 2 diabetes (T2D), whereas T2D patients have higher risk of PD compared to general population. Based on these premises, we evaluated the toxicity of these three toxins on pancreatic β-cell lines (INS-1 832/13 and MIN6) and we showed that rotenone is the most potent for reducing β-cells viability and altering mitochondrial structure and bioenergetics in the low nanomolar range, similar to that found in dopaminergic cell lines. MPP+ and 6-OHDA show similar effects but at higher concentration. Importantly, rotenone-induced toxicity was counteracted by α-tocopherol and partially by metformin, which are endowed with strong antioxidative and cytoprotective properties. These data show similarities between dopaminergic neurons and β-cells in terms of vulnerability to toxins and pharmacological agents capable to protect both cell types.